Generalized multinucleate cell angiohistiocytoma: case report and literature review. (28th November 2016) - Wang, Ming; Abdul‐fattah, Bilal; Wang, Cuiyan; Zhao, Yun; Qu, Xiaoying; Al‐Muriesh, Maher; Wang, Xia; Zhu, Li; Qian, Yue; Huang, Changzheng; Chen, Siyuan
Abstract : Background: Multinucleate cell angiohistiocytoma (MCAH) is an uncommon benign fibrohistiocytic and vascular proliferation, which usually occurs as slow‐growing grouped reddish‐brown to purple papules and nodules on the distal extremities or face. Patients with generalized MCAH are extremely rare and to our knowledge, there are no more than 11 cases reported previously in the medical literature. Objective: To describe the clinical, histopathologic features and immunohistochemical characteristics of all reported cases of generalized MCAH and investigate any potential clinicopathological correlations. Methods: A systematic review of the literature was done with information collected and organized in a table. A new case report is also described in a 42‐year‐old female with generalized MCAH. Histopathologic and immunohistochemical features of multiple biopsies were analyzed. Results: Men and women are equally affected. It is crucial to take multiple biopsies preferably from newly formed lesions to reach the correct diagnosis. The divergent results in immunohistochemistry staining for CD68 and estrogen receptor (ER) alpha necessitate further studies to reach a precise etiology and pathogenesis and secure it with certainty. Conclusion: Awareness of the clinicopathological hallmarks is important to avoid underdiagnosis of MCAH and the immunohistochemical features may contribute to understanding the pathogenesis of this rare disease.